To solve the given equation, we need to perform any needed calculation to isolate X on it.
![(3)/(8)x+7=-(7)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/l3uf27p9ih0nn83bmdh2j0aoha01nms6ld.png)
The first step is to multiply both sides by 8, as follows:
![\begin{gathered} ((3)/(8)x+7)\cdot8=-(7)/(8)\cdot8 \\ \\ 3x+56=-7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ylvxx0oi18uvuemoh309emqozqsa5lr3c1.png)
Now we subtract 56 to both sides:
![\begin{gathered} 3x+56-56=-7-56 \\ \\ 3x=-63 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/neexcnh3l2es9u05g2hqqwi8d9043w38la.png)
Now we divide both sides by 3:
![\begin{gathered} (3x)/(3)=-(63)/(3) \\ \\ x=-21 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zh3lrhn42kg1qj043dvuh7satp7uat70fy.png)
From the solution we developed above, we are able to conclude that the answer of the given equation is:
![x=-21](https://img.qammunity.org/2023/formulas/mathematics/college/jtgajw002frq6sftp2y3brntb37lex1ang.png)